PROSES KOMUNIKASI HUMAS POLDA SUMBAR (Studi Deskriptif Humas Yang Objektif, Dipercaya dan Partisipasi) - Sahman Sahman; Ernita Arif; Elva Rona Ningroem (Centre for Asian Social Science Research (CASSR), FISIP, UIN Bandung, 2019)
This study aims to describe and analyze the process of drafting the message, the process of delivering messages, receiving the message itself for the public and finding obstacles and proposing communication in the form of providing information in the West Sumatra Police Public Relations environment. This research was conducted using qualitative methods. Public Relations in other terms also called Public Relations (PR) is the main branch in the study of communication science. Communication skills are the main things that must be developed both academically and in operational activities. In the world of Public Relations (PR) communication is the main expertise that must be owned by a public relations officer, with the communication expected to have similarities between the organization and the public and the formation of favorable public opinion, so that public relations in West Sumatra Police can promote how the process of communication is objective, trusted and participation.